Anne Frank : a history for today - Metselaar, Menno; Rol, Ruud van der; Anne Frank Stichting (Anne Frank House, 1995)
Photographs, illustrations, and maps accompany historical essays, and diary excerpts, providing an insight to Anne Frank and the massive upheaval which tore apart her world